Elevation of MPF and MAPK gene expression, GSH content and mitochondrial distribution quality induced by melatonin promotes porcine oocyte maturation and development in vitro - Zhao, Zimo (PeerJ, 2020)
The MPF and MAPK genes play crucial roles during oocyte maturation processes. However, the pattern of MPF and MAPK gene expression induced by melatonin (MT) and its correlation to oocyte maturation quality during the process of porcine oocyte maturation in vitro remains unexplored. To unravel it, in this study, we cultured the porcine oocytes in maturation medium supplemented with 0, 10(−6), 10(−9), and 10(−12) mol/L melatonin. Later, we analyzed the MPF and MAPK gene expression levels by RT-PCR and determined the maturation index (survival and maturation rate of oocytes). The GSH content in the single oocyte, and cytoplasmic mitochondrial maturation distribution after porcine oocyte maturation in vitro was also evaluated. We also assessed the effects of these changes on parthenogenetic embryonic developmental potential. The oocytes cultured with 10(−9)mol/L melatonin concentration showed higher oocyte maturation rate, and MPF and MAPK genes expression levels along with better mitochondrial distribution than the 0, 10(−6), and 10(−12) mol/L melatonin concentrations (p < 0.05). No significant difference was observed in the survival rates when the oocytes were cultured with different melatonin concentrations. The expression of the MPF gene in the oocytes cultured with 10(−6) mol/L melatonin was higher than with 10(−12) and 0 mol/L melatonin, and the expression of the MAPK gene in 10(−6) and 10(−12) group was higher than the control (p < 0.05). As far as the embryonic developmental potential is concerned, the cleavage and blastocyst rate of oocytes cultured with 10(−6) and 10(−9) mol/L melatonin was significantly higher than the 10(−12) mol/L melatonin and control. In conclusion, 10(−9)–10(−6) mol/L melatonin significantly induced the MPF and MAPK gene expression; besides, it could also be correlated with GSH content of single oocyte, mitochondrial maturation distribution, and the first polar body expulsion. These changes were also found to be associated with parthenogenetic embryo developmental potential in vitro.